A HEALTHY LIFESTYLE IS THE BASIS FOR A SUCCESSFUL LIFE - Zhuravska, Nataliia; Vitovetska, Arina (Sworld-Us Conference proceedings, 2024)
The importance of sports, keeps our body in good shape, helps to survive heavy physical loads better, helps to adapt ecologically and psychologically in life, to make quick decisions, to control oneself and temper one’s spirit; work on yourself.